Evaluation of the risk of flood in Iskandar Malaysia Region using fuzzy logic and weighted linear combination in Geographic Information System - Yeganeh, Nasim (2013)
Recently, Iskandar Malaysia region have been affected by flood events, which cause environmental, social and economic impacts. Severe rainfall, natural situation, new unplanned developments, and insufficient drainage systems make the situation more remarkable. This research is an approach of flood hazard assessment at regional scale. The objectives of this study are to find out the criteria which contribute to the risk of flooding based on the characteristic of the region to develop a GIS-aided urban flood susceptibility map. Fuzzy logic and Weighted Linear Combination (WLC) methods in Geographic Information System (GIS) are used to achieve the objectives. Defined criteria are evaluated by means of complexity, uncertainty and sensitivity analysis. The methodology emphasizes on uncertainty criteria which contribute to the risk of flood and increase the risk. Distance from main stream, elevation, slope, land use type, distance from river and distance from discharge channel are recognized as effective criteria within the region. Each criterion is evaluated based on fuzzy membership type and generated map are combined using weighted linear combination to produce the final flood susceptibility map. Final susceptibility map indicates that around 6.586 square kilometers within the region face high level of risk. Pulai, Senai Kulai, Tebrau and Johor Bahru can be considered as areas which face the risk. Natural and man-made situation influence the level of risk in each area. Generally the southern part of the region has high level of risk as a consequence of conjunction of location of stream, lowland and land use type. The model is evaluated by sensitivity analysis to analysis the uncertainty and degree of importance of input criteria. Finally the situation in 2025 is investigated based on the proposed plan for 2025.